2014
DOI: 10.1177/0146167214538459
|View full text |Cite
|
Sign up to set email alerts
|

Feeling (Mis)Understood and Intergroup Friendships in Interracial Interactions

Abstract: The present research investigated whether having out-group friends serves as a buffer for feeling misunderstood in interracial interactions. Across three experience sampling studies, we found that among ethnic minorities who have few White friends or are not interacting with White friends, daily interracial interactions are associated with feeling less understood. By contrast, we found that among ethnic minorities who have more White friends or are interacting with White friends, the relationship between daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 36 publications
(49 reference statements)
2
31
0
Order By: Relevance
“…Similar to stories from racial minorities in Germany, statements such as "I couldn't say that I'm German, because the Germans also don't accept it" indicated that exclusion experiences with dominant-culture members stood in the way of feeling like a valuable member of society and were a source of distress (Hubbard & Utsey, 2015). Perceiving high levels of ethnic discrimination led to fewer possibilities for positive interactions with the dominant culture (Shelton, Douglass, Garcia, Yip, & Trail, 2014), to less bicultural orientation (Vedder et al, 2007), and to a stronger heritage orientation and disidentification with the dominant culture (Benet-Martínez & Haritatos, 2005;Pasupathi, Wainryb, & Twali, 2012). As part of a highly stigmatized group, such as a Muslim woman wearing a headscarf, the strong sense of heritage-culture belonging was a cultural resilience factor potentially shielding the negative effects of exclusion and discrimination on well-being (Branscombe, Schmitt, & Harvey, 1999;Rivas-Drake & Stein, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to stories from racial minorities in Germany, statements such as "I couldn't say that I'm German, because the Germans also don't accept it" indicated that exclusion experiences with dominant-culture members stood in the way of feeling like a valuable member of society and were a source of distress (Hubbard & Utsey, 2015). Perceiving high levels of ethnic discrimination led to fewer possibilities for positive interactions with the dominant culture (Shelton, Douglass, Garcia, Yip, & Trail, 2014), to less bicultural orientation (Vedder et al, 2007), and to a stronger heritage orientation and disidentification with the dominant culture (Benet-Martínez & Haritatos, 2005;Pasupathi, Wainryb, & Twali, 2012). As part of a highly stigmatized group, such as a Muslim woman wearing a headscarf, the strong sense of heritage-culture belonging was a cultural resilience factor potentially shielding the negative effects of exclusion and discrimination on well-being (Branscombe, Schmitt, & Harvey, 1999;Rivas-Drake & Stein, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were compensated $50 after completing the study. Data from the Youth Experience Study have been published elsewhere (Douglass and Yip 2015; Douglass et al 2014; Shelton et al 2014; Yip 2014, 2015; Yip et al 2013). …”
Section: Methodsmentioning
confidence: 99%
“…As young people move through adolescence, their social environments become increasingly complex (Bronfenbrenner & Morris, ). Adolescents' feelings toward their ethnic/racial groups (Kiang, Yip, Gonzales‐Backen, Witkow, & Fulgni, ; Yip & Fulgni, ) and social interactions (e.g., intragroup and intergroup contact; Shelton, Douglass, Garcia, Yip, & Trail, ; Yip, Douglass, & Shelton, ) also vary substantially from situation to situation and day to day. Given these variations and complexities, whether and how parental cultural socialization translates into long‐term development through adolescents' daily experiences is an open question.…”
Section: Parental Cultural Socialization and Ethnic/racial Private Rementioning
confidence: 99%